1077. Heart Transplantation as Salvage Treatment for Intractable Infective Endocarditis. (26th November 2018) - Tattevin, Pierre; Muñoz, Patricia; Moreno, Asuncion; Hékimian, Guillaume; Delahaye, François; Duval, Xavier; Castel, María Ángeles; Hasse, Barbara; Jamarillo, Natalia; Vincelj, Josip; Wray, Dannah; Mestres, Carlos; et al.
Abstract: Background: Infective endocarditis (IE) remains a severe disease with contemporary in-hospital mortality rates of 20%. Although valvular replacement is performed in 50% of patients during the acute phase, heart transplantation remains the last resort in selected patients with extensive perivalvular lesions or end-stage cardiac failure. Methods: Cases were identified through the International Collaboration on Endocarditis (ICE) network. All patients who underwent heart transplantation during the acute phase of IE, with at least three months follow-up, were enrolled. Data were extracted from medical charts on a standardized questionnaire. Only patients who fulfilled Duke criteria for definite IE were enrolled. Results: Between 1991 and 2017, 19 patients (6 women, 13 men), with a median age of 52 years (interquartile range, 41–61) underwent heart transplantation for IE refractory to optimized medical treatment and/or other cardiac surgery in Spain ( n = 9), France ( n = 6), and Colombia, Croatia, Switzerland, and the United States (one patient each). IE affected prosthetic ( n = 10), native valves ( n = 9), primarily aortic (56%), and mitral (28%). Pathogens were oral streptococci ( n = 7), Staphylococcus aureus ( n = 5, including two methicillin-resistant), Enterococcus faecalis ( n = 2), and Mycoplasma hominis, Haemophilus para-influenzae, Candida albicans (one patient each). Two cases were not documented. Main cardiac lesions were vegetations ( n = 17), severe regurgitation ( n = 15), peri-annular abscesses ( n = 9), prosthetic valve desinsertion ( n = 4), and intra-cardiac fistula ( n = 1). Seventeen patients underwent cardiac surgery at least once before transplantation, and four patients were on circulatory assistance (left ventricular assist-device, or extra-corporeal membrane oxygenation, two patients each). Median delay between first cardiac surgery and transplantation was 28 days (IQR, 18–71). Six patients died (32%), including four during the first month post-transplant. Thirteen patients survived, with a median follow-up of 44 months post-transplantation (IQR, 13–88). Conclusion: Heart transplantation may be considered as salvage treatment in highly selected patients with intractable infective endocarditis. Disclosures: All authors: No reported disclosures.